Círculos de cultura e podcasts como educação libertadora no ensino médio do Colégio Militar Tiradentes II em Imperatriz-MA - OLIVEIRA, Jéssica Ruane Lima de (2022)
The present research work seeks to work the action research on Popular Education with the use of Information and Communication Technologies (TDICs), based on Paulo Freire's Pedagogy. The research is set at Colégio Militar Tiradentes II in Imperatriz- Maranhão, with high school classes. The tools used were the culture circles, based on the conceptions of Paulo Freire, who directed the study to the production and execution of a podcast, based on situations – problems – challenges, which, through debate, enabled the construction of words generators. The product of this will be a documentary with the compilation of the most golden moments of the intervention. This work has been carried out with the aim of presenting Paulo Freire's Pedagogy with the interaction with new technologies, which can be used to increase Popular Education. As an action research, the character of the research is interventional, and it is during this intervention that the research was constituted, according to the needs of the investigative process. In this sense, the research was expanded and documented, which also resulted in a product that can be shared and used to collaborate even more with Popular Education.